The impact of IFRS on the value relevance of accounting data of banks listed on the Warsaw Stock Exchange - Piotr Bolibok (Copernican Journal of Finance & Accounting, 2014)
The paper aims at investigating the impact of IFRS on the value relevance of fundamental accounting data announced by banks listed on the Warsaw Stock Exchange over the period 1998–2012. Given the specificity of banking sector, the analyses were based on the Ohlson residual income valuation model. The empirical evidence indicates that observed increase in the value relevance of both book values of equity and residual incomes of banks after introduction of IFRS is statistically insignificant. The obtained results are, therefore, consistent with the findings of previous research conducted on non-financial enterprises in the context of Polish capital market.